Analysis of sealing ability of endodontic cements apical plugs - Cechella, Bruna (J Clin Exp Dent, 2018)
BACKGROUND: It is unknown whether the bioactivity of Biodentine characterized by the precipitation of hydroxyapatite and formation of tags into the dentinal tubules improve its sealing ability as an apical plug. Aim: To evaluate the sealing ability provided by Biodentine and mineral trioxide aggregate (MTA) apical plugs, with or without phosphate-buffered saline (PBS) intracanal dressing, using a glucose leakage method. MATERIAL AND METHODS: The space of the canal of 100 root segments with about 12 mm long was shaped using Gates-Glidden. After created an apical retrograde cavity, the root segments were randomly divided into 4 groups (n = 25): G1 – Biodentine; G2 - Biodentine + PBS intracanal dressing; G3 - MTA and G4 - MTA + PBS intracanal dressing. All access openings were filled with temporary cement and all root segments were introduced in floral foams moistened with PBS. After 2 months, all root segments were prepared to evaluate the glucose leakage. The amount of glucose leakage was quantified by a spectrophotometer and the data were analyzed using chi-square test (p<0.05). RESULTS: Traces of the glucose were observed in a higher of samples that received Biodentine apical plug (p<0.05). The exposure to intracanal PBS did not influence the sealing provided by Biodentine and MTA. CONCLUSIONS: The Biodentine had lower sealing ability than MTA. The interaction with PBS intracanal dressing did not improve the sealing ability provided by sealers. Key words:Apexification, dental cements, dental leakage, glucose, pressure.